Six decades of ethnic minority population change in China. Issue 2 (4th May 2019) - Wu, Jiaping; Ingram, Catherine
ABSTRACT: China's 55 non-Han ethnic minority groups were at least in part politically and institutionally 'invented' by China's ethnic classification project, and also through the effects of the system of continuous population census. This paper investigates population change of the non-Han ethnic minorities (NHEMs) over the past six decades. The number of NHEMs as a whole tripled from 1953 to 2010. However, growth has differed among individual groups and in different time periods. The population of some groups has fluctuated while that of others has grown steadily, regardless of the size of the groups. As a whole, since 2000 the growth rate of NHEMs has been lower than that of the Han Chinese, and the population of 13 NHEM groups has begun to decline. A growing number of people belonging to ethnic minorities have switched their ethnic identities to Han. This has especially been the case for NHEM youth. The change in ethnic minority populations has been influenced by dynamic interactions among demographic factors, ethnic identification as well as political, economic and policy changes.